A fit for purpose training programme for the decontamination of personnel. (13th March 2015) - O'Mara, E; Cole, P; Wynn, A; Collison, R
Abstract: Contingency plans are a crucial part of operating any nuclear facility. The success of a contingency plan depends on the efficacy of the plan and the confidence and understanding of those who must enact it. This project focused on both of these aspects, clarifying technique and then designing and delivering a training programme for decontamination. The design of the training was based on the IAEA Systematic Approach to Training (SAT). The delivery focused on ways of increasing retention including use of practical examples and assessment, peer assessment and visual contingency plans. A quantitative survey of the trainees was conducted using a questionnaire before and after the training programme delivery. The results clearly demonstrate an improvement across all elements of skills and knowledge required to undertake decontamination. Effective training is fundamental to the development of a good safety culture and the methodology used in this work has led to a clear improvement in radiation protection culture at the Devonport site.